Solidification and stabilization of asbestos brake lining dust using polymeric resins - Chan, Y.M.; Mahalingam, R.; Agamuthu, Pariatamby (2000)
Two polymeric resins, Polymal and Hetron, were evaluated to solidify/stabilize (S/S) for ultimate disposal brake lining dust containing asbestos. This dust was generated as part of a sequence of processing steps in the manufacture of automobile brake linings. The mean grain size of the lining dust for disposal was 298.2 mu m, the range being from 24.9 to 567.3 mu m. Based on the Toxicity Characteristic Leachability Procedure (TCLP) and the American Nuclear Society (ANS) 16.1 (modified) leach protocols, although the untreated lining dust contained high concentrations of Zn, Ba, Pb, Fe, Cu, and Cr, solidification with Polymal and Hetron respectively reduced the leachable fraction of these heavy metals in the lining dust to less than 14 and 18%, compared to untreated control; and the heavy metal concentrations in the TCLP leachate were below the permissible limits set by the Malaysia Environmental Quality Act (EQA) (1974), the Environment Quality (Sewage and Industrial Effluents) Regulations (1979), as well as the USEPA regulatory limit fur TCLP. The final pH of the extract from the untreated dust ranged from 4.92 to 4.95, whereas when polymeric resins were used, the pH increased to between 5.1 and 5.2. When the ANS 16.1 (modified) leach test was performed, the leaching rate was highest for Zn, followed by Ba and Pb, while the leaching of Cr, Cu, and Fe was too low for detection. The observed linear relationship between the cumulative fraction leached (CFL) and the square root of the leaching time in all polymer resin treated samples indicates that the mechanism of leaching is mainly through diffusion. The Leachability Index (Li) obtained ranged between 9 and 10, which exceeds the guidance value of 6, clearly indicating that the heavy metal retention within the solidified matrix is quite effective. The hardening time when polymeric resins were used ranged anywhere from 1.5 to 12 h, and this decreased as the amount of MEK Peroxide initiator was increased. Compressive strength of the brake lining solid matrix was between 53 and 68 MPa, which was much higher than the standard guidance limit for polymeric resin solidification. Between the two resins, Polymal shows better performance in terms of heavy metal retention capability, whereas Hetron exhibits higher compressive strength. Despite the attractive performance features of either of the resins, S/S with either of them appears to be prohibitively expensive for the current Malaysian regulatory marketplace, although attractive elsewhere.